Perancangan Aplikasi Project Management Berbasis Web di PT. Aurora Arta Indonesia - Iqbal Prabu Juliantoro (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
One of the main challenges encountered is the suboptimal project progress tracking system, and the frequent delays in progress reporting that hinder management in monitoring project development. Therefore, the author will write a thesis discussing the creation of a web-based project management application using the PHP programming language and the Laravel framework. The development process of this software will use the waterfall method. This application is expected to facilitate PT. Aurora Arta Indonesia in conducting its business processes. With features for progress tracking, billing recording, and progress reporting to clients, it will help achieve project goals quickly and effectively.